2014
DOI: 10.1007/s40094-014-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

Soliton reflection in a magnetized inhomogeneous warm plasma: effect of ionization

Abstract: The reflection of nonlinear solitary waves is studied in a plasma under the effect of an external magnetic field and constant ionization along with finite ion temperature. To investigate the reflection of solitary waves, relevant modified Korteweg-deVries equations for the right and left going waves are derived, and coupled at the point of reflection for obtaining the expression of reflection coefficient. The solitary waves are found to shift after their reflection. Variation of reflection coefficient and shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Kuehl investigated theoretically the reflection of ion acoustic soliton, and showed that a shelf develops behind the soliton and the reflected wave is small compared with both trailing shelf and soliton amplitude decrease due to energy transfer to the shelf [17][18][19]. Then after, many authors took the problem of soliton propagation in inhomogeneous plasma in different physical situations like plasma with finite ion temperature [20,21], with negative ions [22][23][24][25], with dust [26] and trapped electrons [27], in magnetic field [28,29], with non isothermal electrons [30], with ionization [31,32], with electron inertia contribution [33] and also in other contexts [16,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Kuehl investigated theoretically the reflection of ion acoustic soliton, and showed that a shelf develops behind the soliton and the reflected wave is small compared with both trailing shelf and soliton amplitude decrease due to energy transfer to the shelf [17][18][19]. Then after, many authors took the problem of soliton propagation in inhomogeneous plasma in different physical situations like plasma with finite ion temperature [20,21], with negative ions [22][23][24][25], with dust [26] and trapped electrons [27], in magnetic field [28,29], with non isothermal electrons [30], with ionization [31,32], with electron inertia contribution [33] and also in other contexts [16,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…We start from the constant coefficient KdV equation (51) which have an exact one solitary wave solution as…”
Section: Exact One Solitary Wave Solution With Variable Velocitymentioning
confidence: 99%
“…The reflection of ion acoustic soliton due to plasma inhomogeneity has been explored for various experimental conditions in [29][30][31][32][33][34][35]. Kuehl et al [36][37][38] theoretically investigated the reflection of ion acoustic soliton followed by a series of works in different physical situations like plasma with finite ion temperature [39,40], with negative ions [41][42][43][44], with dust [45] and trapped electrons [46], in a magnetic field [47,48], with non isothermal electrons [49], with ionization [50,51], with electron inertia contribution [52] and also in other contexts [35,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Studying the behavior of solutions of inhomogeneous case merits a separate investigation using tools of soliton theory, which is our future task. The application of our results might be particularly interesting in the investigations in homogeneous and inhomogeneous space and laboratory plasma [32][33][34][35][36].…”
Section: Conclusion and Remarksmentioning
confidence: 99%